P1-06. Two CIDP patients with anti-CNTN1 IgG4 antibodies and nephrotic syndrome. Issue 9 (September 2017) - Kokubun, Norito; Nagashima, Takahide; Funakoshi, Kei; Komagamine, Tomoko; Hirata, Koichi; Yuki, Nobuhiro
Abstract : Previous studies showed that CIDP patients with anti-CNTN1 IgG4 antibodies form a specific subtype, which shows subacute progression and poor prognosis. In contrast, nephropathy has been recognized as a rare complication in CIDP and other immune-mediated neuropathies. We here describe two CIDP patients with anti-CNTN1 IgG4 antibodies and nephrotic syndrome. The patients were 35- (P1) and 69-year-old (P2) males. Both patients developed subacute course of sensory and motor neuropathy. In parallel with neuropathy course, nephrotic syndrome was present. Nerve conduction studies revealed severe demyelinating polyneuropathy. The disease showed resistance to IVIg, cortico steroids, plasma exchange and cyclosporine, and the severe sensory disturbance and muscle atrophies were left. High titer of anti-CNTN1 IgG4 antibodies was detected in their serum. Renal biopsy in P1 showed membranous nephropathy with the deposition of IgG1 and IgG4 on the glomerular-basement membrane. These findings arise a possibility of existence of shared antigen between peripheral nerve and renal glomerular-basement membrane.